KINEMATIC CHARACTERISTICS OF THE APPROACH RUN ON HANDSPRING VAULT BY HIGH LEVEL MALE GYMNASTS HIGH LEVEL MALE GYMNASTS - Costas Dallas; George Dallas; Kalenia Papazogonopoulou; Apostolos Theodorou (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
The approach run is a fundamental precondition for successful vault performance, as it enables the gymnast to develop maximum controlled horizontal velocity. The purpose of this study was to investigate the length, frequency, and velocity of steps during the run-up phase (approach run) in the execution of the handspring vault on the vaulting table. Nine high-level male artistic gymnasts, who performed the handspring vault under training conditions, volunteered to participate in the study. Five video cameras-four stationary and one scanning-were used to record the run-up phase, the hurdle step, and the take-off from the springboard. The gymnasts performed six trials of the handspring vault with a three-minute rest between each trial. Results showed that the final step was shorter than the penultimate step, and the penultimate step was longer than the preceding step. Additionally, the gymnasts demonstrated a gradual increase in their run-up velocity, a key requirement for a successful jump, up to the penultimate step. The average step frequency among gymnasts ranged from 3.20 to 4.88 steps per second, while the average step velocity across the six attempts was between 4.03 and 7.37 m/sec. Finally, a gradual increase in the gymnast's velocity was observed up until the last step, with the final step being shorter than the penultimate step and the penultimate step being longer than the one before it.